Pluralitas Tradisi Sebagai Pemersatu Keberagaman (Unity of Diversity) Di Desa Plumbon, Yogyakarta - Abdul Mujib (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2021)
In Yogyakarta, there are areas that have their own uniqueness about managing people’s diversity. The tradition (ritual) practiced by the people in Plumbon Village is an important part as a unifying difference from the diversity of religions and social communities. This study found a reinforcing factor for the reapengellization of a harmonious society, even though the community is heterogeneous both religiously and socially. Practically, mutual respect when celebrating certain religious traditions together is a construction that must be maintained so that the harmony of a plural society such as in Plumbon Village is sustainable and beneficial for the people and the harmonious state of Indonesia.